Analisis Komparatif Model Pembelajaran Project Based Learning (PjBL) dan Problem Based Learning (PBL) dalam Meningkatkan Keterampilan Berpikir Kritis - Jauhari Manasik; Fatoni, Imam; Nasrulloh, Nasrulloh (https://journal.metanusantara.com/pedagogia, 2025)
21st-century education demands the development of critical thinking skills, yet classroom practices are still dominated by less effective conventional methods. This quasi-experimental study aimed to analyze the difference in effectiveness between Project-Based Learning (PjBL) and Problem-Based Learning (PBL) models in enhancing the critical thinking skills of high school students. The data sources were 90 students of class XI Social Studies at a public high school in Bojonegoro Regency, divided into three groups: PjBL, PBL, and control. Data were collected using a validated structured essay test and analyzed using ANCOVA. The results showed that: (1) There was a significant difference in critical thinking skills between the experimental groups (PjBL and PBL) and the control group; (2) Comparatively, the PjBL model proved significantly more effective than the PBL model in improving students' critical thinking skills. These findings indicate that while both constructivist models are effective, the product-oriented nature of PjBL has a more powerful impact on training synthesis and evaluation, the highest levels of critical thought. This study recommends that educators consider PjBL as a primary strategy to optimize the development of 21st-century competencies.